Patients', family members' and healthcare staffs' opinions about existential issues as a base for an educational intervention. Issue 1 (1st June 2011) - Henoch, I; Danielson, E; Strang, S; Browall, M; Melin-Johansson, C
Abstract : Objective: To explore patients', family members' and healthcare staff's opinions about existential issues important to patients with cancer and their relatives. Methods: Two integrative literature reviews were conducted about existential issues among cancer patients and relatives, and interventions to meet these issues. Four focus groups were conducted with healthcare staff working with cancer patients at different stages about patients' existential issues, and staff's responsibility when existential issues are raised. Results: In the patient review, existential issues were divided into two themes: struggle to maintain self-identity and threats to self-identity. Relatives' existential issues concerned living both in and beyond the presence of death, with reminders of death, compelling them to respond to life close to death and seek support. Few interventions directed to patients or relatives applicable to everyday healthcare practice were found. Focus groups with staff revealed four categories of patients' existential issues, life and death, meaning, freedom of choice, relationships and solitude. According to staff, their responsibility concerned achieving an encounter with the patient. Conclusion: Results from three studies are congruent in that, patients, relatives and staff agree, although in different ways, about the importance of existential issues to patients and relatives. Healthcare staff was aware of the importance of existential issues and are to some extent confident about how to act when these issues are raised by the patients. Ongoing studies: The project group now continues implementing findings from these studies in an educational intervention to healthcare staff in different settings, and planning interventions to patients and relatives.